2017
DOI: 10.1017/s0007485317000931
|View full text |Cite
|
Sign up to set email alerts
|

Host-location behavior of the tea green leafhopper Empoasca vitis Göthe (Hemiptera: Cicadellidae): olfactory and visual effects on their orientation

Abstract: The tea green leafhopper, Empoasca vitis Göthe, is one of the most serious pests in tea growing areas. This study investigated the roles played by olfaction and vision in host orientation behavior. The compound eye of E. vitis was found to be a photopic eye; few olfactory sensilla were found on the antennae, while abundant gustatory sensilla were recorded on the mouthparts. Three opsin genes (EV_LWop, EV_UVop, EV_Bop) were isolated and found to be mainly expressed in the compound eye compared with other parts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 21 publications
1
10
0
2
Order By: Relevance
“…Opsin is the central factor that influences the phototactic behavior of many insects. In the tea green leafhopper, dsEV_LWop and dsEV_Bop exhibited a higher inhibitory effect on tropism behavior . Surprisingly, in honeybee knock‐down of the long‐wavelength receptor does not significantly change the physiological properties of the retina .…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Opsin is the central factor that influences the phototactic behavior of many insects. In the tea green leafhopper, dsEV_LWop and dsEV_Bop exhibited a higher inhibitory effect on tropism behavior . Surprisingly, in honeybee knock‐down of the long‐wavelength receptor does not significantly change the physiological properties of the retina .…”
Section: Discussionmentioning
confidence: 90%
“…Apposition eyes exhibit the characteristics of high resolution and low optical sensitivity, which are helpful for diurnal insects . Many diurnal insects use the visual sense as the primary component of host‐plant location . Within the tree canopy, the olfactory and auditory senses are used to search for flush leaf and mates .…”
Section: Introductionmentioning
confidence: 99%
“…Little was known about the modalities of E. onukii oviposition behavior [18,19]. The results of this study indicated that most of the eggs were laid within the 3rd and 4th leaf order interval classes, whereas a low proportion of the eggs were detected within the leaf order interval classes below the 4th leaf order interval.…”
Section: Discussionmentioning
confidence: 65%
“…For example, chemical stimuli from the foliage of cotton could only be detected by Empoasca devastans from 1 cm, but visual stimuli were effective at up to 3.6 m (i.e., vision is the only option for E. devastans from a range from 1 cm to 3.6 m) [ 7 ]. Odors from the host were unable to attract E. vitis over long distances (>20 cm), across which visual cues (color) are the dominant information for E. vitis in selecting habitat [ 8 ]. Visual cues may play an important role in habitant location at a distance for E. vitis adults.…”
Section: Introductionmentioning
confidence: 99%